Three essays regarding the impacts of legalization of marijuana on housing and historical population theory - Rasmussen, Jorgen August Skriver, author; Weiler, Stephan, advisor; Pena, Anita Alves, committee member; Pressman, Steven, committee member; Schaller, Zachary, committee member; Burkhardt, Jesse, committee member (Colorado State University. Libraries, 2022)
Chapter 2 looks at the novel question of whether legal marijuana dispensaries' insufficient access to banking institutions has affected home prices in Denver County, Colorado. Presently, little research exists regarding legalized marijuana's impact on home prices in Colorado. Yet such research suggests legalization positively affects such prices (Burkhardt & Flyr, 2019) (Cheng, et al., 2018) (Conklin, et al., 2020). However, mechanisms by which marijuana legalization might affect home prices are not investigated. It is well-established that banks are unable and unwilling to do business with state-legalized marijuana dispensaries (Hudak, 2020). Hence, we hypothesize that dispensaries are investing cash in the housing market. We avail ourselves of tried-and-true hedonic modeling for such analysis. In so doing, we discover a statistically significant positive correlation between the quantity of recreational marijuana revenue generated and home prices in Denver County, Colorado. Our research is novel both in its thoroughness and accuracy of the data employed. To the best of our knowledge, we are the first to utilize historically accurate housing characteristics and unique economic controls in the analysis of marijuana and home prices in Denver, Colorado (Burkhardt & Flyr, 2019) (Cheng, et al., 2018) (Conklin, et al., 2020). Additionally, our study appears to represent the first consideration of implications arising from the juxtaposition of state vs. federal legal status of marijuana. As such, our research holds insights for policymakers. Chapter 3 resumes our investigation of the possible implications of legalized marijuana for housing. Specifically, Denver County home resale probabilities and any associations they might have with marijuana revenue generated. Research has presented evidence that there exists a distinct possibility of dispensaries investing in the Denver housing market (Cheng, et al., 2018) (Rasmussen, 2021). Navarro (2013) and Seefried (2019) suggest that if dispensaries are purchasing houses, it may be for money laundering purposes. However, there is reason to believe that dispensaries have incentives to retain purchased homes for either legitimate rental purposes or more nefarious grow house uses (Schaub, 2016) (Snowden, 2020). To investigate such possibilities, we employ both logit and probit probability models. Such models are used to determine any potential association between changing amounts of legal marijuana revenue and Denver home resale probabilities. We find a statistically significant rise in property resale rates associated with increased recreational marijuana revenue. Thus, our results fit the type of money laundering activity discussed by Navarro (2013) and Seefried (2019). Consideration of the impacts of the legalization of marijuana on home resale probabilities appears absent in the literature. Thus, our work has import for policymakers. In particular, there are implications for affordable housing availability. Together with Cheng, et al. (2018) and Rasmussen (2021), our findings bode ill for Denver County affordable housing. This is especially true as marijuana demand continues to grow while banking access remains largely absent. Our final chapter considers the Marquis de Condorcet's six assumptions on population growth. Such a model of population development is presented in Esquisse d'un Tableau Historique des Progress de L'Esprit Humain. In addition, we examine the original principles and outcomes of the Malthusian population model. Such an undertaking is done to discover what conclusion Malthus' model would arrive at had the views of Condorcet been incorporated. Another important aspect of our work is investigating why Malthus's essay disagreed with the Marque de Condorcet's propositions on population. Finally, we conclude our efforts by examining empirical and historical scholarly inquiry regarding which of the population models history favored. To our knowledge, only the work of Winch (1996) comes close to our investigation. However, Winch (1996) presents a hypothetical meeting of Malthus and Condorcet, intended to discuss general differences and common ground these men possessed. However, Winch (1996) fails to consider implications for the Malthusian population model of Condorcetian population theory. Thus, our research is innovative in discovering Malthus as a man of his times and Condorcet as a scryer of the distant future of population growth.
Keywords: hedonic model; home resale probabilities; marijuana legalization; home prices; Condorcet; Malthus